2020
DOI: 10.1186/s12883-020-01985-w
|View full text |Cite
|
Sign up to set email alerts
|

Elevated blood urea nitrogen is associated with recurrence of post-operative chronic subdural hematoma

Abstract: Background Chronic subdural hematoma (CSDH) is fundamentally treatable with about a 2–31% recurrence rate. Recently, there has been renewed interest in the association between Blood Urea Nitrogen (BUN) and intracranial lesion. Therefore, this paper attempts to show the relationship between BUN and CSDH recurrence. Methods A total of 653 CSDH cases with Burr-hole Irrigation (BHI) were enrolled from December 2014 to April 2019. The analyzed parameters included age, gender, comorbidities, laboratory investigati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…This study indicated associations between elevated activated partial thromboplastin time (APTT), prothrombin time (PT) and international normalized ratio (INR) and worse outcome [17]. Reduced levels of serum fibrinogen in cases manifesting recurrence of cSDH compared with non-recurrence cases were indicated in the univariate analysis conducted by Wang et al [25].…”
Section: Cytokinesmentioning
confidence: 82%
See 2 more Smart Citations
“…This study indicated associations between elevated activated partial thromboplastin time (APTT), prothrombin time (PT) and international normalized ratio (INR) and worse outcome [17]. Reduced levels of serum fibrinogen in cases manifesting recurrence of cSDH compared with non-recurrence cases were indicated in the univariate analysis conducted by Wang et al [25].…”
Section: Cytokinesmentioning
confidence: 82%
“…In the largest prospective cohort study identified (653 patients), blood urea nitrogen (BUN) levels and additional variables (PLTs, fibrinogen, leukocytes, erythrocytes, hemoglobin, creatinine) were analyzed [25]. The authors indicated that elevated postoperative BUN levels (> 6.4 mmol/L) was the only measure independently associated with cSDH recurrence [25].…”
Section: Other/miscellaneousmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our previous report, all patients underwent standard BHI surgery with general anesthesia ( 27 ). Briefly, a single burr hole was drilled, and irrigation of the hematoma with normal saline was subsequently performed.…”
Section: Methodsmentioning
confidence: 99%
“…In recent decades, numerous predictors for recurrence have been suggested, including epidemiological characteristics, radiological findings, clinical symptoms, and even laboratory values: Examples of such prognostic factors are higher age, male sex, hypertension, anticoagulants, hyperdense hematoma components or midline shift on preoperative imaging, and also elevated blood urea nitrogen or low levels of high-density lipoprotein. However, the results between various studies have remained conflicting and partly contradictory [13,26,31,33,34,44,46]. Especially the effects of antithrombotics Alexander Younsi and Lennart Riemann contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%